The Influence of Green Accounting, MFCA, and Environmental Performance on Sustainable Development - Aprilia Dwi Mahfida; Omi Pramiana (Proceeding International Conference on Digital Education and Social Science, 2025)
The purpose of this study is to examine how green accounting, material flow cost accounting (MFCA), and environmental peformance affect sustainable development in food and beverage manufacturing firms listed on the Indonesia Stock Exchange between 2022-2024. A quantitative research design was applied. The study population consisted of 95 companies, from which 50 were selected as samples using purposive sampling. Data were analyzed through descriptive statistics, classical assumption testing, multiple linear regression, and hypothesis testing using SPSS 20. The results show that all three variables positively and significantly affect sustainable development. These findings demonstrate that adopting environmental accounting practices, optimizing material flow efficiency, and enhancing environmental performance substantially contribute to strengthening corporate sustainability efforts. Overall, the study underscores the strategic role of environmental management and sustainability-oriented accounting in improving sustainability outcomes within the food and beverage manufacturing industry.